PENGARUH PROFESIONALISME, PENGETAHUAN TENTANG PENGELOLAAN KEUANGAN, DAN INTENSITAS PEMBINAAN DANA TERHADAP KUALITAS KEUANGAN DI KAMPUNG PASIR BAGADEU - Lestari, Tita; Yumartono (Sekolah Tinggi Ilmu Ekonomi GICI, 2023)
The purpose of this study was to determine and analyze the influence of professionalism, knowledge of financial management, and the intensity of fundraising on financial quality in Kampung Pasir Bagadeu. The type of research used is explanatory research with the research method of collecting data using a questionnaire. The data analysis model used is multiple linear regression analysis. Sample selection was done by purposive sampling. The sample is 100 respondents, using multiple linear regression analysis. The results of the Determination Coefficient Test show that the independent variables in the form of professionalism, financial management and fund management jointly affect the dependent variable of financial quality reaching 84.8% while the remaining 15.2% is influenced by other variables not included in this study, for example environment, land tax payment order, financial socialization, fund security and so on. While the F test shows that the independent variables consisting of professionalism, financial management and fund management simultaneously have a significant effect on financial quality with the results of the analysis Fcount = (371.401) > Ftable = (2.70). The results of the t test show that the variable professionalism (19.416), financial management (5.054), fundraising (5.481) where ttable (1.668) means that partially these variables have a significant effect on financial quality in Kampung Pasir Bagadeu.